2022
DOI: 10.3390/ijms232415488
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of P-glycoprotein and Breast Cancer Resistance Protein Expression Induced by Focused Ultrasound-Mediated Blood-Brain Barrier Disruption: A Pilot Study

Abstract: The blood-brain barrier (BBB) controls brain homeostasis; it is formed by vascular endothelial cells that are physically connected by tight junctions (TJs). The BBB expresses efflux transporters such as P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP), which limit the passage of substrate molecules from blood circulation to the brain. Focused ultrasound (FUS) with microbubbles can create a local and reversible detachment of the TJs. However, very little is known about the effect of FUS on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…It should, however, be noticed that only a partial -45% decrease in P-gp expression was achieved. This result is consistent with previous studies reporting a significant but partial down-regulation of P-gp at the BBB from 24h to 48h after FUS [17][18][19][20]. These studies used different acoustic pressure and FUS conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It should, however, be noticed that only a partial -45% decrease in P-gp expression was achieved. This result is consistent with previous studies reporting a significant but partial down-regulation of P-gp at the BBB from 24h to 48h after FUS [17][18][19][20]. These studies used different acoustic pressure and FUS conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have consistently reported a significant decrease in the expression of P-gp at the BBB from 24h to 48h after FUS [17][18][19][20]. However, it remains to be evaluated whether delayed FUS-induced down-regulation of the P-gp may locally enhance the brain delivery of P-gp substrates.…”
Section: Introductionmentioning
confidence: 98%
“…This restricted passage of antitumor drugs through the BBB is mainly attributed to active efflux transporters (AETs) [ 194 ]. P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) are the two most common AETs that are associated with drug resistance in multiple tumors and limit the brain penetration of antineoplastic drugs [ 195 ]. More than half of the commercially available antitumor drugs are recognized by P-gp, which prevents drug entry into the brain parenchyma via the transcytosis pathway.…”
Section: Exosomes In Tumor Therapymentioning
confidence: 99%
“…This leads to the loosening of tight junctions in between endothelial cells, allowing large molecules to enter the brain in the sonicated area (Hynynen et al 2001, Sheikov et al 2004, Cammalleri et al 2020. In addition, MB-assisted focused-US can also alter the gene expression of essential BBB efflux transport proteins, such as downregulation of the P-glycoprotein, which enhances medication localization in the parenchyma (Aryal et al 2017, Jangjou et al 2021, Conti et al 2022. However, it is difficult to understand the precise mechanism of interactions between MB and tissues leading to BBB disruption (Barzegar-Fallah et al 2022).…”
Section: Introductionmentioning
confidence: 99%